Serial multiple crossed immunoelectrophoresis at a microscale: A stamp‐sized 2D immunoanalysis of protein C3 activation caused by nanoparticles. Issue 17 (9th August 2016) - Coty, Jean‐Baptiste; Varenne, Fanny; Vachon, Jean‐Jacques; Vauthier, Christine
Abstract : Crossed immunoelectrophoresis (C‐IE) is used to detect and quantify specific proteins. An application allowed the evaluation of complement system activation by nanomaterials. The work aimed to improve the C‐IE toward a higher throughput and less tedious method. A new concept was implemented to prepare and run agarose gels. The first and the second dimension of electrophoresis were performed on a single gel plate, prepared before the beginning of the analysis. Several samples were migrated simultaneously on the same migration line. Up to 35 analyses were run at once, providing stamp‐sized electrophoregrams (2.8 × 3 cm 2 ) maintaining the performance of the original method performed on 5 × 7 cm 2 gel slabs. Robustness and precision of the method were demonstrated through a validation approach using ANOVA. Handling, experimental duration, amount of reagents, and overall cost of one analysis were considerably reduced compared to the original method. With the same equipment, seven times more analyses can be performed in one run. C‐IE can be used to analyze many types of proteins. The new experimental modalities were suitable for the application developed in the present work that was to evaluate activation of protein C3 of the complement system triggered by nanomaterials.